1999
DOI: 10.1002/(sici)1098-2744(199907)25:3<219::aid-mc8>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of arsenic(III) and chromium(VI) on nuclear transcription factor binding

Abstract: The toxic metals arsenic(III) and chromium(VI) are considered human carcinogens, although they may act through different mechanisms. We previously showed that when administered at single low, non-overtly toxic doses, chromium, arsenic, and several other chemical carcinogens preferentially alter expression of several model inducible genes in both whole-animal and cell-culture systems. In this study, we assessed whether chromium and arsenic target specific signaling pathways within cells to selectively modulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Further analysis of upstream regulators and network revealed four hub factors, Nr2f2, Jun, Kras and ApoE (Figure 3). Moreover, many transcription factors, such as Prox1, Nr1d1, Rxrg, Hlf, Nr0b2, Foxm1, Nfn1a, Jun, Junb, Fox3, Etv5, Sqtm1, and NF-kB1b were differentially regulated by arsenic exposure in our data, consistent with reports in mammalian cells, where the AP-1 complex, NF-kB, and the MTF-1 (metal-responsive transcription factor 1) could be activated by arsenic [69][72].…”
Section: Discussionsupporting
confidence: 91%
“…Further analysis of upstream regulators and network revealed four hub factors, Nr2f2, Jun, Kras and ApoE (Figure 3). Moreover, many transcription factors, such as Prox1, Nr1d1, Rxrg, Hlf, Nr0b2, Foxm1, Nfn1a, Jun, Junb, Fox3, Etv5, Sqtm1, and NF-kB1b were differentially regulated by arsenic exposure in our data, consistent with reports in mammalian cells, where the AP-1 complex, NF-kB, and the MTF-1 (metal-responsive transcription factor 1) could be activated by arsenic [69][72].…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with in vitro studies, increased AP‐1 DNA binding activity was also reported in urinary bladder epithelium of mice chronically exposed to high concentrations of iAs III (5–100 mg/L) in drinking water (42). Activating effects of iAs III on c‐Jun and c‐fos expression or AP‐1 DNA binding have been confirmed in HeLa cells (12), human embryonic kidney (HEK 293) cells (43), human breast cancer (MDA‐MB‐435) and rat hepatoma (H4IIE) cells (10), and mouse epidermal (Cl 41) cells (16), and in precision‐cut rat lung slices (44). The concentrations of iAs III used in these studies ranged from 0.1 to 300 I M. Notably, activation of c‐Jun and c‐fos expression or AP‐1 DNA binding has been observed almost exclusively at concentrations above 10 IM iAs III .…”
Section: Discussionmentioning
confidence: 90%
“…In addition, iAs modifies signal transduction pathways that are involved in the regulation of cell growth and proliferation (6). It has been shown that iAs III modulates the expression and/or DNA binding activities of several transcription factors associated with cell proliferation and death, including nuclear factor‐κB (NF‐κB) (7, 8), tumor suppressor 53 (p53) (9), a GC‐box specific transcription factor Sp1 (10), a Y‐box specific transcription factor‐1 (YB‐1) (10), and activator protein‐1 (AP‐1) (11‐13). Examination of mechanisms involved in the AP‐1 activation indicates that iAs III stimulates the mitogen‐activated protein kinase (MAPK) cascade, thus inducing expression of c‐Jun and c‐fos protooncogenes and enhancing DNA binding activity of AP‐1 (12, 1417).…”
mentioning
confidence: 99%
“…Studies have shown that As (III) modulates the expression and DNA binding activities of various transcription factors associated with cell proliferation and cell death including tumor suppressor 53 (p53), nuclear factor-kB (NF-κB), a Y-box specific transcription factor-1 (YB-1), activator protein-1 (AP-1), and a GC-box specific transcription factor 1(SP-1) [Salazar et al, 1997; Barchowsky et al, 1996; Kaltreider et al, 1999; Simenova et al, 2000]. Available data suggest that As (III) may modulate AP-1 dependent gene transcription and contribute to either induction of cell proliferation or acceleration of cell death [Simenova et al, 2000; Trouba et al, 2000].…”
Section: Introductionmentioning
confidence: 99%